'Seeking permission': an interviewing stance for finding connection with hard to reach families. Issue 2 (13th July 2011) - Aggett, Percy; Swainson, Mary; Tapsell, Dave
<x xml:space="preserve">Abstract</x> The systemic therapy literature is dominated by clinic‐based accounts of therapy. The work of an outreach, home‐based therapy team is described, in a tradition of systemic therapies which directly seek to challenge service access constraints and social injustice. In paying careful attention to the micro‐interactions of initial contact, seeking permission is suggested as an interviewing stance for connecting with families who are not engaged with services, where there have been histories of partner violence.